2014
DOI: 10.3389/fimmu.2014.00536
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Functional Genomics and the Bovine Macrophage Response to Strains of the Mycobacterium Genus

Abstract: Mycobacterial infections are major causes of morbidity and mortality in cattle and are also potential zoonotic agents with implications for human health. Despite the implementation of comprehensive animal surveillance programs, many mycobacterial diseases have remained recalcitrant to eradication in several industrialized countries. Two major mycobacterial pathogens of cattle are Mycobacterium bovis and Mycobacterium avium subspecies paratuberculosis (MAP), the causative agents of bovine tuberculosis (BTB) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 104 publications
(122 reference statements)
2
23
1
Order By: Relevance
“…The comparison of M. bovis- or M. tuberculosis-infected macrophages with respect to non-infected macrophages revealed a sequential increase in the number of DE genes across the infection time-course, which peaked at 48 hpi and a larger number of DE genes were seen in M. bovis -infected macrophages with the exception of 6 hpi (Fig.3A, B, C, Supp_VI.csv); similar temporal expression profiles were previously reported in other in vitro bovine and human macrophage infection studies (42, 72-74). Comparison of these DE gene lists identified a subset of genes that displayed the same directionality and a similar magnitude of expression (Fig.4A) (Supp_VII.csv).…”
Section: Resultssupporting
confidence: 87%
“…The comparison of M. bovis- or M. tuberculosis-infected macrophages with respect to non-infected macrophages revealed a sequential increase in the number of DE genes across the infection time-course, which peaked at 48 hpi and a larger number of DE genes were seen in M. bovis -infected macrophages with the exception of 6 hpi (Fig.3A, B, C, Supp_VI.csv); similar temporal expression profiles were previously reported in other in vitro bovine and human macrophage infection studies (42, 72-74). Comparison of these DE gene lists identified a subset of genes that displayed the same directionality and a similar magnitude of expression (Fig.4A) (Supp_VII.csv).…”
Section: Resultssupporting
confidence: 87%
“…It has been shown that pathogenic M. bovis may survive during a stage where neither growth nor killing is seen within macrophages, suggesting a ‘latent’ infection; it has also been speculated that M. bovis may infect an animal and persist in this stage without progression until reactivation 8 , 9 . The successful survival of M. bovis within bovine macrophages may rely on a diverse succession of immunomodulatory mechanisms, including the blockade of bactericidal nitric oxide (NO) production and apoptosis, leading to a strong generation of necrosis 10 , 11 , 12 …”
mentioning
confidence: 99%
“…8,9 The successful survival of M. bovis within bovine macrophages may rely on a diverse succession of immunomodulatory mechanisms, including the blockade of bactericidal nitric oxide (NO) production and apoptosis, leading to a strong generation of necrosis. [10][11][12] Susceptible cattle become infected with M. bovis when housed with infective cattle, by contact with wildlife reservoirs or when exposed to a contaminated environment with favourable conditions for the pathogen, such as slow air exchange, large herd size or overcrowding and warm weather. 1, [13][14][15] Whatever the source of M. bovis, infection of cattle and spread within the herd is highly probable when it is endemic, especially when it is highly prevalent.…”
mentioning
confidence: 99%
“…Macrophages provide a safe niche for long‐term survival within mammals (Andrade et al ., ), however, within the lower eukaryotes organisms, FLA are also hosts to several Mycobacterium species, including M. bovis (Mardare et al ., ). The current growing interest in amoebae as important mediators of emerging epidemics of human and animal diseases (Rue‐Albrecht et al ., ; Scheid, ) stimulated these studies on the persistence of M. bovis within amoebae as a potential environmental source of TB infection.…”
Section: Discussionmentioning
confidence: 99%
“…including M. bovis (Taylor et al, 2003;Greub et al, 2004;Mba Medie et al, 2011). There are striking similarities in the biology of FLA and macrophages, the established eukaryotic intracellular niche within host organisms of mycobacteria (Rue-Albrecht et al, 2014). Trophozoites are the actively replicating and feeding form of FLA with similar phagocytic capacity to macrophages (they can uptake particles and microorganisms larger than 0.5 lm) and are capable of forming enveloping phagocytic vacuoles followed by formation of phagolysosomes which, in some cases, kill and digest both pathogenic and nonpathogenic microbes (Guimaraes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%